Sociology of literature; Human awareness; Social criticism. - M. Howailid (PT. Habe Cendekia Utama, 2025)
Literature functions as a dynamic social document that reproduces existential experiences and societal conflicts, including structural inequality, discrimination, and collective trauma. This study aims to describe literary reflections on the realities of human life through a critique of injustice; analyze the mechanisms of empathy development through conflict and trauma; and demonstrate literature's contribution as a moral transformation that strengthens social awareness. A qualitative approach using literature review and content analysis of Swingewood and Ratna's sociology of literature was used. Primary data were from the novel Malam Seribu Jahanam (Paramaditha, 2023), the poetry of Cak Nun (2016), and Merdeka Karena Hati (Fuadi, 2019); secondary data were from the journal 2025. Descriptive-analytical analysis with triangulation focused on intrinsic elements and extrinsic functions. Literature has educational, reflective, socially critical, emancipatory, and empathetic functions to build human awareness. Representation is through characters with inner conflict (70%), themes of suffering (85%), repressive settings (60%), and emotional metaphors (90%). In a socio-educational context, literature is relevant for awareness-raising (80%) and the Independent Curriculum, integrated as character-building material.